SAT0319 Description of musculoskeletal symptoms in a cohort of patients with psoriasis. (12th June 2018) - Magee, C.; Farkas, F.; Ikumi, N.; Szentpetery, A.; Gallagher, P.; Kirby, B.; Fitzgerald, O.
Abstract : Background: The BIOmarkers of COMorbidities (BIOCOM) in Psoriasis (Pso) study is a longitudinal study which aims to identify clinical, genetic or protein biomarker features associated with the development of co-morbidities, notably Psoriatic Arthritis (PsA) in patients with Pso. Pso usually precedes the development of PsA with an average interval of 10 years. Thus, Pso patients are an ideal group in which to study the early events in the evolution to PsA. Objectives: Herein we describe the baseline clinical features in this BIOCOM cohort. Based on these features, we categorise patients into groupings which may be helpful during long-term follow-up. Methods: Patients are being recruited from the dermatology clinics at St. Vincent's University Hospital, Dublin. Inclusion criteria included a diagnosis of Pso with disease duration of less than 10 years and an age of 18 years or older. Patients with another serious active medical illness, a previous diagnosis of inflammatory arthritis or those who were receiving systemic immunosuppressant therapy for Pso were excluded Following recruitment, patients were assessed for musculoskeletal (MSK) signs or symptoms: questionnaire detailing history of any MSK complaints including inflammatory back pain, full physical examination including evidence of tender or swollen joints and entheseal tenderness (using the Leeds Enthesitis Index) and routine blood testing including inflammatory markers. If patients had any MSK findings they underwent routine radiographs, MRI scanning or ultrasound scanning as indicated. Patients were then categorised using all information available as follows: Pso only; Pso+: MSK signs or symptoms but insufficient for diagnosis of PsA; PsA (CASPAR): Diagnosis of PsA meeting CASPAR criteria; Other Rheumatic Disease. Results: To date 190 patients with Psoriasis have been recruited. Of those, 9 were excluded due to a diagnosis of Pso >10 years previously. One was excluded due to a previous diagnosis of JIA Of the remaining 180 patients: 106 were male (58.9%). Mean age was 41.5±14.8 years. Average duration of Pso: 6.1±2.9 years. On examination: 126 (70%) had psoriatic nail disease (pitting, ridges or onycholysis). 84 patients had no musculoskeletal signs or symptoms. The remaining 96 patients had at least one musculoskeletal finding as outlined in table 1 below. Conclusions: Analysis of patients recruited to date for the BIOCOM-Pso study shows that at baseline at least one third of patients with Pso had non-specific MSK signs and symptoms. Previous studies suggest these patients may be more likely to subsequently develop PsA. By following this cohort prospectively, we hope to better characterise which features are predictive of the development of PsA in patients with Pso. Disclosure of Interest: None declared